On interpretation and task selection in studies on the effects of noise on cognitive performance - Sörqvist, Patrik (Frontiers in Psychology, 2014)
Cognitive tasks are not “process pure”. Rather, task scores reflect the contribution from many cognitive processes. For example, reading comprehension involves sub-processes such as inference making, suppression/inhibition of irrelevant text interpretations, working memory, etc. In this paper, I discuss the theoretical and methodological consequences of the “process impurity” problem to studies on the effects of noise on cognitive performance. Theoretical problems arise when the effects of noise on complex tasks are interpreted as reflecting an impairment of a specific cognitive skill/process. Moreover, as long as the goal is to quantify and understand noise effects as they become manifest in applied settings (like schools and offices), both theoretical and methodological problems arise when more “process pure” tasks (e.g., the Stroop task) are employed instead of (complex) tasks that are representative for the applied setting of concern. It is argued that cognitive noise researchers should employ representative noise, representative tasks (which are necessarily complex/process impure) and interpret the results on a behavioral level of analysis rather than on a cognitive level of analysis.